Wells and Illfare: Conditions and Characteristics of Groundwater Irrigation in Tamil Nadu - Janakarajan, S.; Moench, Marcus (Water Nepal, 2009)
The Authors argue that the degradation of Tamil Nadu's groundwater resource base through over extraction and pollution is increasing rural poorly, social inequality and conflict. They present an overview of growth of groundwater irrigation in India to support their argument and highest problems that have emerged in other regions. They conclude the paper with respect to both Tami Nadu and the country as a whole and explore policy options. Keywords: wells; ground water Water Nepal Vol. 12, No. 1&2, 2006 Page: 47-80